The TTIP, ISDS and the shift towards transparency in investor-state arbitration - Ihalainen, Anna-Karoliina (fi=Turun yliopisto|en=University of Turku|, 2016)
The negotiations between the EU and the US over the Transatlantic Trade and Investment Partnership (TTIP) have generated a lot of discussion about investor-state dispute settlement (ISDS). This discussion provided the inspiration for this thesis, with the TTIP in the background, setting the scene. In this thesis I study the nature of ISDS and the principle of transparency within investor-state arbitration. I aim to determine whether the use of ISDS is restricted to international arbitration and whether ISDS can be considered to constitute a system or regime. Furthermore, I consider whether the introduction of the UNCITRAL Rules on Transparency in Treaty-based Investor-State Arbitration (2014, the UNCITRAL Transparency Rules) changes investor-state arbitration in relation to transparency. To achieve this, I examine ISDS provisions in several different international investment agreements (IIAs) and evaluate the ways in which transparency is incorporated into investment law. Moreover, I compare the provisions on transparency and confidentiality in institutional arbitration rules with the UNCITRAL Transparency Rules. I have formed several conclusions, including that the ISDS provisions may contain methods other than international arbitration and that ISDS does not constitute a system. Furthermore, the UNCITRAL Transparency Rules do change – theoretically, at least – investor-state arbitration to become more transparent. Whether the UNCITRAL Transparency Rules will make investor-state arbitration fully transparent depends on the actions of the contracting state parties when negotiating new IIAs and whether they choose to incorporate the UNCITRAL Transparency Rules in the IIAs already concluded.